METAL DYNAMICS IN A TROPICAL WATERSHED: THE SÃO FRANCISCO RIVER AND ITS COMPARTMENTS - Torres, Isabela Claret; Horn, Adolf Heinrich; Lemos, Rodrigo Silva (Geochimica Brasiliensis, 2019)
Water ecosystems are one of the most threaten environments due to anthropogenic pressures, among them the contamination of metals that are toxic to every life form. The main objective of this paper was to investigate the role of each compartment of a river system in metal dynamics using metal sediment concentration. To accomplish the objective sediments from several sites in a tropical river drainage basin were sampled comprising different types of compartments: : the river channel, the dry and wet inundation area and marginal lagoons, as well a pristine site with no anthropogenic impact. A Principal Component Analysis and the calculation of the Enrichment Factor and Index of Geoacummulation were conducted. The results showed that was no great difference of Index of Geoaccumulation among the different compartments. However, the Enrichment Factor was higher in wet inundation areas followed by dry soils from inundation areas and dry lagoons. Principal Component Analysis selected the metals Fe, Cu and Mg in axis 1, while axis 2 selected Mg and Ba. Although there was not a clear separation in the results of the multivariate analysis among sites across a transect, the analysis separated the compartments in relation to the concentration of metals. The results showed that each compartment had its own dynamics in relation to accumulation of metals present in the river basin. The study shows the importance of studying different types of habitats of a drainage basin to stablish best management practices.